FUNGSI KEPEMIMPINAN PENDIDIKAN ISLAM - ., Suarga (Jurnal Pendidikan Kreatif, 2020)
Leadership or leadership is the art and skills of people to use their power to influence others to carry out certain activities that are directed at the goals set. Leading is to work intentions for a particular purpose, but carried out by others. People who are led are people who are governed, influenced, and regulated by provisions that apply formally or non-formally. Leadership is the nature of the leader in carrying out his duties and obligations as well as his responsibilities morally and legally formally for all the exercise of authority that has been delegated to the people they lead. Thus, leadership is more functional that will be distinguished by certain types. Leadership is also the implementation of the skills to manage others as their subordinates, managing human resources and organizational resources in general. Islamic education leadership is an ability to encourage or influence within the scope of the implementation of education for the achievement of the objectives of education effectively and efficiently in accordance with the word of Allah, and the words of the Prophet. In its activities the leader has the power to direct and influence his subordinates in connection with the tasks carried out